2022
DOI: 10.3389/fgene.2022.909245
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis-Related Genes Associated With Immune Activity and Prognosis of Colorectal Cancer

Abstract: This study aims at screening out the key necroptosis-related genes in colorectal cancer and elucidating the role of necroptosis-related genes in the immune activity and prognosis of colorectal cancer (CRC). The CRC patients’ data were downloaded from The Cancer Genome Atlas (TCGA). The non-negative matrix factorization method was applied to identify new molecular subgroups. Survival analysis and single sample Gene Set Enrichment Analysis were performed to determinate the differences in the overall survival tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We acquired necroptosis-related genes (NRGs) from the GSEA (M24779.gmt), KEGG pathway (hsa04217), and previous studies [ 15 , 16 ]. We ultimately identified 204 NRGs in the present study (Table S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…We acquired necroptosis-related genes (NRGs) from the GSEA (M24779.gmt), KEGG pathway (hsa04217), and previous studies [ 15 , 16 ]. We ultimately identified 204 NRGs in the present study (Table S2 ).…”
Section: Methodsmentioning
confidence: 99%
“… 10 , 41 It has been reported that m6A plays an increasingly important role in various physiological and pathological processes in various cancers, 42 including pancreatic cancer, 43 breast cancer, 44 and our published CRC study. 45 While the roles of various programmed cell death (PCD) modes in CRC prognosis have been explored in the literature, these models have primarily focused on individual modes of cell death, such as the apoptosis-related prognostic signature, 46 autophagy-related signature, 47 , 48 , 49 , 50 , 51 cuproptosis-related signature, 52 , 53 , 54 ferroptosis-related signature, 55 , 56 , 57 necroptosis-related signature, 58 , 59 and pyroptosis-related prognostic signature. 60 , 61 , 62 , 63 , 64 , 65 However, the interplay between m6A modification and PCD in CRC prognosis remains unexplored, representing a gap in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism is conformable to apoptosis and morphology analogous to necrosis. Necroptosis-related genes are strongly associated with TME of CRC, and patients carrying these gene changes may benefit from immunotherapy and have better prognosis of the disease ( 30 ).…”
Section: Discussionmentioning
confidence: 99%